Golygon - Ros, Manon Steffan (Y Lolfa, 2017)
Personal and piercing essays by Manon Steffan Ros, one of Wales' best contemporary authors. The essays, which deal with various topics such as People, Culture, Places and Suffering comprise comprise material which appeared originally in her weekly column in Golwg.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books